Answer:
a. x = 6000 - 200p
b. E(p) = p / (p - 30)
c. E(15) = -1
d. %change in Δ = -20p/30-p
Step-by-step explanation:
P + 0.005x = 30
a. P + 0.005x = 30
-P -P
0.005x = 30 - p
We divide both side by 0.005
0.005x = 30 - p
0.005 0.005
x = 30 - p / 0.005 -----> x = 6000 - 200p
b. E (b) = b/x * dx/dp
x = 6000 - 200p
dx/dp = -200
E(p) = p/x (-200)
E(p) = p / 6000 - 200p * (-200)
E(p) = p / 200(30-p) * (-200)
Cross through by the 200
E(p) = p / (30 - p)
E(p) = p / (p - 30)
c. E(p) = p / (p - 30)
E(15) = 15 / (15-30)
E(15) = 15 / -15
E(15) = -1
This implies that if price increases 1 units, then demand goes down by 1 unit.
d. dx/dp = -200
Δx = dy/dp Δp = (-200) 20p/100
Δx/x = -40/x = -40P / 6000 - 200p
%change in Δ = Δx/x * 100 = -40p/60 - 2p
%change in Δ = -20p/30-p